First Report of Black Fig Fly, Silba adipata (Diptera: Lonchaeidae), in the United States. Issue 1 (29th April 2022) - Britt, Kadie E; Gordon, Phoebe E; Faber, Ben A; Rios, Sonia I; Wilson, Houston
Abstract: The black fig fly, Silba adipata McAlpine (Diptera: Lonchaeidae), is a Mediterranean insect that exclusively reproduces on figs, Ficus carica L. (Rosales: Moraceae). Widely considered a pest of figs throughout southern Europe, North Africa, and the Middle East, S. adipata was recently discovered infesting figs throughout southern California, representing the first report of this pest in the United States. Here, we provide background information on the distribution, biology, ecology, monitoring, and management of this pest, as well as outline research and extension efforts that have been catalyzed by this recent invasion. California accounts for a majority of both fresh and dried fig production in the United States. To date, S. adipata infestations have been limited to orchards in coastal and southern California, whereas most commercial fig production takes place in the inland Central Valley region. Better knowledge of temperature thresholds is currently needed to estimate potential range expansion to these more inland regions of the state.